Analysis of Income Elasticities of Brazil’s Energy Matrix - Perroni, Marcos Gonçalves; Da Costa, Sérgio Eduardo Gouvêa; Da Silva, Wesley Vieira; De Lima, Edson Pinheiro; Da Veiga, Claudimar Pereira (International Journal of Energy Economics and Policy, 2016)
This study aims to estimate and analyze the income elasticities of Brazil’s energy matrix, represented by the supply and consumption of energy. We sought to compare the income elasticities of both energy products and consumption through secondary sources and consumer sectors. This is an explanatory or relational research of an ex-post-facto nature, analyzing the period from 1970 to 2011, using the ANCOVA-EC estimation method. The results obtained from the estimates show that both for energy products, as in relation to industrial sectors, the elasticities are statistically different. The naphta, natural gas and ethyl alcohol had the highest elasticities in the energy matrix, and the industries ferro-alloy, non-ferrous metals and non-energy are the most sensitive to income growth. When elasticities are compared with the sectoral energy intensity index, there is evidence that less efficient sectors have higher income elasticities. In summary the results show that there is sectors or products that are more sensitive to economic growth where the energy-intensive and demand presented as the main factors to explain the sensitivity, there is also evidence to demonstrate that the level of efficiency is different compared the different sectors. Keywords: Income Elasticity, Price Elasticity, Energy Matrix, Sector Demand for Energy JEL Classifications: E3, G38, K23, M48, Q4